NOTA SÔBRE A INFESTAÇÃO EXPERIMENTAL DO AUSTRALORBIS NIGRICANS (SPIX) DO MUNICíPIO DE SÃO PAULO, PELO SCHISTOSOMA MANSONI - Coutinho, J. O. (Arquivos da Faculdade de Higiene e Saúde Pública da Universidade de São Paulo, 1956)
An attempt was made to infect Australorbis glabratus and Australorbis nigricans with Schistosoma mansoni. The experiments were not successful when using snails brought directly from endemic areas: A. nigricans from Santos (São Paulo) and A. glabratus from Recife (Pernambuco) and Jacarezinho (Paraná). The complete cycle of the trematode in snails, to the stage of cercariae, was observed in experiments with specimens bred in the laboratory: A. glabratus from Recife (Pernambuco) and A. nigricans from the City of São Paulo. The author is of the opinion that there is no transmission of Schistosoma mansoni in the City of São Paulo and vicinities due to the following facts: A. nigricans has little susceptibility to the infection, the climatic conditions are not favorable to the evolution of the parasite in the intermediate host and the density of that snail is low in the area.